THE EFFECT OF COMMUNICATIVE APPROACH ON SPEAKING ACHIEVEMENT - Ilyas S.Pd., M.Pd. (Universitas Islam Negeri Alauddin Makassar, 2017)
This paper aims at finding out whether or not communication Approach affect students’ achievement in speaking class. This research was experimental research, which aims to find out the effectiveness of communicative approach for improving the process of English language teaching and learning. The population of this research were the fourth semester of STAIN Watampone which consists of 44 students. From this number, the research took 22 students randomly as the sample of the research. Those students were divided into two classes, namely 11 students in experimental class and 11 students in the control class. The instrument of this research was observation checklist and speaking test. Communicative approach can improve students’ speaking achievement at STAIN Watampone. It was indicated by the result of t test that the t- observation was higher than t-table value, where t- observation = 2,204> t- table = 2.086, at .05 levels of significance with a degree of freedom of 20. This data indicates that there is a significant difference between students’ speaking achievement taught by using communicative approach than taught by using conventional method. It could be stated that the application of communicative approach in teaching speaking could improve the students' speaking achievement better than the conventional applied.